AutistiCare: a one-stop centre for parents with Autism Spectrum Disorder children in Perlis - Zakaria, Noor Azura; Tajuddin, Nur Syazwana; Mohd Supian, Nur Faraayuni Sufea (IIUM Press, 2024)
Individuals with Autism Spectrum Disorder (ASD)typically struggle with social communication and interaction, psychomotor, activity daily living, cognitive, as well as behavioural and intention issues. It is difficult for parents and carers of children with ASD to manage their difficulties, particularly at home and at school. This going to be worst if the parents or carers are not well-equipped with related knowledge on the ASD management. The COVID-19 pandemic situation that spread the world in 2020 has caused significant mental health challenges for parents, such as anxiety and depression, as a result of additional challenges in coping with their children in everyday life, in which the usual therapies that they received at the therapy centre must be completed at home. As a result, supporting them in managing this problem is critical to improving their psychological well-being as a continual attempt from the therapy centre to home. Society nowadays is adapted to the use of the technologies because of COVID-19 phenomena. Strong evidence suggests that online intervention is equally important with a face-to-face approach that has positive effects to autistic children and provides psychological support for the parents. However, there is a gap on the digital intervention platform according to the needs of parents for ASD management especially in Perlis society. Therefore, the purpose of this project is to invent a telehealth platform, characterized as the delivery of healthcare to patients and caregivers via the Internet. The proposed system is AutistiCare targeting parents with ASD children in Perlis that will be developed through a web-based system. The system includes various intervention modules, such as online communities, including online consultations between experts and parents, psychological support through forums, psychoeducation delivered via learning materials such as videos or modules, and service-related postings such as advertisements for ASD programs or seminars. It is envisaged at the end; the system is equipped with optimal ASD management content to support parents with autistic children in Perlis. In addition, it can be a platform to seek knowledge and assistance from the expert remotely.